"A New Species": Neighborhood and Community Shopping Centers in St. Louis Park, Minnesota, 1941-1956 - Anderson, Lauren (My University, 2017)
This thesis examines a topic often overlooked by historians of suburbanization and consumption: the influence of neighborhood and community shopping centers in postwar suburban communities. Conceived during the 1920s and 30s, these centers became ubiquitous features of the American landscape during the postwar era. This thesis examines the neighborhood and community shopping centers developed in St. Louis Park, a suburb of Minneapolis, Minnesota, between 1941 and 1956. Centers constructed in St. Louis Park largely mirrored national trends in shopping center development, confirming the limited research compiled by other authors. Using St. Louis Park as a case study, this thesis argues that the economic impact of neighborhood and community centers on preexisting forms of suburban retail was limited, suggesting that it was not until the development of regional shopping centers in the mid-1950s that shopping centers posed a serious threat to freestanding suburban retail.
Keywords: Shopping centers--United States; Shopping centers--Minnesota; Retail trade--United States; Retail trade--Minnesota